Diseño de un Modelo de Gestión de Mantenimiento basado en la confiabilidad para los equipos más críticos de Litografía Moravia S.A., que permita una mejora del departamento de mantenimiento y una disminución de los costos asociados a paros productivos. - Gómez-Martínez, José Pablo (Instituto Tecnológico de Costa Rica, 2018)
The company Litografía Moravia S.A., develops its operations in the design and printing of the graphic arts since 1992, where the printing is made by the offset method which has as principle the printing of indirect form in the sheets of paper. The developed project seeks the improvement of the Maintenance Department of this company, and likewise the reduction of productive stoppages through the design of a Maintenance Management Model based on Reliability. As a methodology, we first proceeded to evaluate the current state of the company through the COVENIN 2500-93 standard, which allowed us to determine the current state of the maintenance department, which in turn will serve as a starting point for the objectives, strategies and improvements for the Maintenance Department. Then, the Semi-quantitative Method was used to rank the teams through risk (CTR, for its acronym Total Criticity for Risk), this criticality analysis will allow to determine the hierarchy of the teams in the company based on the current state of the organization and of the assets, this in order to facilitate future decisions for the design of maintenance plans and define the resources of the company according to the importance or criticality of the teams in the process. Based on the critical equipment, the maintenance plans are designed using the RCM tool (Reliability Centered Maintenance), this tool is used because it conveniently determines the maintenance needs of the asset, which represents a high complexity for the precision and accuracy that this machinery must have to make the impressions. As a result, scheduled maintenance routines were obtained for the assets and the determination of the stock of spare parts that the company must have in the warehouse. Said programming of the routines was defined by means of the Reliability, Availability and Maintenance (CDM) analysis, which probabilistically provided the most adequate times to perform maintenance on the presses and it was possible to identify the frequencies of the maintenance inspections for them, with the objective of avoiding scenarios of unavailability (failures) that cause significant production stoppages. In order to maintain control over the execution and evaluation of maintenance, the Integral Scorecard (BSC Balance Score Card) was prepared, which was established according to the needs and objectives of the company, under the VDI-2893 Standard. In this way it will be possible to monitor the efficiency of the processes and maintenance costs. Also, an assessment of the possible renewal of two (2) of the obsolete critical equipment was made, calculating the Annualized Total Cost (CTA) as a technical-financial tool that determined the total expected costs for a useful life today, either a new asset versus another used but functional, with a term of 20 years, and thus provide options to Litografía Moravia SA to make decisions in the near future. When designing the MGM of the project, continuous improvement of the project is contemplated, which is why it proposes different strategies that allow an improvement in the maintenance organization and the efficiency of the proposed management. Within the recommended strategies is the implementation of Total Productive Maintenance (TPM), since this contemplates certain elements that will contribute to the improvement of maintenance within the company and the incorporation of the pillars will allow a coupling between the other departments of the organization. Finally, the estimated costs of the Maintenance Management Model were obtained and compared with the losses calculated by performing only corrective maintenance during the study period of one year, and thus have a projection of savings through the proposed project, to search generate positive results for Litografía Moravia S.A., remain competitive
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Confiabilidad; Gestión de mantenimiento; RCM; Offset; Artes; Research Subject Categories::TECHNOLOGY::Industrial engineering and economy::Other industrial engineering and economics